Klever kicks a smart assistance shoes for blind - Zamry, Danial Iskandar; Yazit, Puteri Eyriena Maysara; Mohd Isa, Marsya Hanisah; Norzaid, Siti Athirah; Roslan, Mohamad Arief Haziq (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
The world is sometimes can be seen as a cruel and dangerous place for people with disabilities especially people that have lost their eyesight and becomes blind. As blind people are not able to see anything and they need some kind of device that can help them to walk and do other things in their daily life like normal people. The traditional device that has been used by blind people for many centuries is a stick to predict the obstacle near them according to (Strong, 2009)[8]. As research keep being developed, the assistance device for the blind people keep changing, in order to improve the effectiveness of the device. Our problem statement for this project is that, blind people sometimes become careless even though they are using traditional assistance device such as stick and this can lead to the great danger to their life. According to Direct Researcher, Christopher Hogan, from 2001 to 2004, on average, 40 blind people were hospitalised as the result of pedestrian accident (Hogan, 2008)[6]. Even though this issue can be considered as minor issue among our society, but it can be much worse in the future. In order to prevent and handle this issue, we invent a technological shoes, given name, "Klever Kicks". Basically, this shoes has two main purposes of its existence. Firstly, this shoes is able to assist the blind people whenever they are walking and secondly, this shoes is going to generate electric energy whenever it's user are walking. Technically, this shoes has two main mechanisms to make it become a functional device. The first mechanism act as energy producer which it is responsible as energy producer that can convert the kinetic energy into electric energy. The second mechanism of Klever Kicks is the ultrasonic sensor mechanism. The sensor mechanism is basically the most important component in this project which it can predict the obstacle or wall that is closed to the user by emitting a buzzer sound. The innovation of Klever Kicks can be seen as a unique and very effective product as we are using simple Arduino Board and it can convert the kinetic energy into electric energy by the help of piezoelectric effect. Klever Kicks is expected to become a high demand product as it is a product that can increase the effectiveness of assistance device for blind people with the help of technological device. This project is predicted to give public awareness to the society that it is important to develop the technology that are clean and do not contaminate environment as the Klever Kicks can generate electric energy without using any hazardous fuel. As the optimistic generation, it is important for us to make research and develop clean energy technologies that are safe to environment and future.